Feasibility Assessment of Converting Forest Into Palm Oil Plantation and Its Implication for Forest Policy and Palm Oil Sustainability Challenges: A Case Study in Melawi Regency of West Kalimantan Province, Indonesia - Yani, Akhmad (Frontiers in Sustainable Food Systems, 2020)
The massive development of oil palm plantations puts significant pressure on forest converting in Melawi Regency, West Kalimantan Province. This is supported by the target of opening 200,000 ha of new oil palm plantations in West Kalimantan Province until 2034. Meanwhile, deforestation is the most critical climate change issue in tropical countries including Indonesia. This research examines the feasibility of clearing forest areas to be converted to palm oil plantations. This research employs the insurance approach to assess the benefits of forest ecosystems. Based on the calculation of the cost-benefits of financial and environmental feasibility, it is found that the protection of forest ecosystems is more feasible than opening palm oil plantations. However, based on the socio-economic cost-benefit calculation results, it is found that opening palm oil plantations is more feasible to implement than ecosystem protection activities. Finally, from the calculation of the total benefits-cost financial, environmental, and socio-economic feasibility, it is found that forest ecosystem protection activities are more feasible to implement than opening palm oil plantations. Another finding stated that an opening of 10,000 ha forest area for palm oil plantations would cause 6.4401 times more damage than the benefits that might be obtained if 10,000 ha of forest area ecosystem is not converted into a palm oil plantation area.